Immobilization in polyvinyl alcohol hydrogel enhances yeast storage stability and reusability of recombinant laccase-producing S. cerevisiae - Herkommerová, Klára; Zemančíková, Jana; Sychrová, Hana; Antošová, Zuzana (Biotechnology letters, 2018)
OBJECTIVES: To improve the storage stability and reusability of various yeast strains and species by immobilization in polyvinyl alcohol (PVA) hydrogel particles. RESULTS: Debaryomyces hansenii, Pichia sorbitophila, Saccharomyces cerevisiae, Yarrowia lipolytica, and Zygosaccharomyces rouxii were immobilized in PVA particles using LentiKats technology and stored in sterile water at 4 °C. The immobilization improved the survival of all species; however, the highest storage stability was achieved for S. cerevisiae and Y. lipolytica which survived more than 1 year, in contrast to free cells that survived for only 3 months. Tests of the reusability of immobilized recombinant laccase-secreting S. cerevisiae revealed that the cells were suitable for repetitive use (55 cycles during 15 months) even after storage in water at 4 °C for 9 months. A suitable method for killing immobilized laccase-secreting cells without affecting the produced enzyme activity was also developed. CONCLUSIONS: The immobilization of yeasts in PVA hydrogel enables long-term, cheap storage with very good cell viability and productivity, thus becoming a promising approach for industrial applications.
Keywords: Reusability; Yeasts; Immobilization; Cells, Immobilized; Preservation, Biological; mikrobiální viabilita; Recombinant Proteins; LentiKats; Polyvinyl Alcohol; Microbial Viability; polyvinylalkohol; Equipment Reuse; Storage stability; rekombinantní proteiny; biotechnologie; lakasa; Biotechnology; imobilizované buňky; ochrana biologická; Saccharomyces cerevisiae; Laccase; opakované použití vybavení; Polyvinyl alcohol hydrogel; Cell Culture Techniques; buněčné kultury